Multistage rifting evolution of the Colorado basin (offshore Argentina): Evidence for extensional settings prior to the South Atlantic opening - Lovecchio, Juan Pablo (2018)
The identification of three independent rifting events in the Colorado basin area highlights the complexity of its Mesozoic rifting history, which ended in the Early Cretaceous with the opening of the South Atlantic Ocean. A first rifting event, associated with the extensional reactivation of previously compressive thrusts of the Ventania-Cape fold belt, is transected by faults forming the main depocenters of the Colorado and possibly the adjacent Salado basin. The second and main rifting stage is correlated with the Early Jurassic Karoo rifting. In the Early Cretaceous, WNW–ESE extension produced NNE-trending landward-dipping faults, concentrated in the outer 100–200 km of the continental crust domain, possibly coeval with SDR emplacement. This is the first identification of three superimposed rifting settings in the southern South Atlantic realm and is key to understanding the complex Mesozoic breakup history of SW Gondwana.